PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS MICROSOFT OFFICE POWER POINT BERBANTUAN APLIKASI POWER DIRECTOR PADA MATERI GETARAN DAN GELOMBANG DI KELAS VIII SMP NEGERI 9 PONTIANAK - margaretha kurniati pati; adi pramuda; nurussaniah nurussaniah (IKIP PGRI Pontianak, 2022)
The development of learning videos based on microsoft office power point assisted by the power director application on vibration and wave material helps teachers deliver material to be more practical which can trigger students' understanding to more easily understand the concept of vibration and wave material. This study aims to: determine the level of feasibility of learning video materials and media based on microsoft office power point assisted by the power director application on vibration and wave material, and determine student responses to learning videos based on microsoft office power point assisted by the power director application on vibration and wave material. This research is a research and development (RD) that uses the ADDIE model. The ADDIE model consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation, but this study only reached the development stage because this study was only limited to testing the feasibility level of learning video products developed based on the validation of material experts, media experts, and responses. student. The instrument used in this research is a questionnaire. Product validation was carried out by material experts and media experts, and tested on 22 students.The results showed that the development of learning videos based on microsoft office power point assisted by the power director application on vibration and wave materials for class VIII SMP was said to be suitable for use in the learning process. The feasibility of learning videos based on material experts got an average score of 85% with very decent criteria, based on media experts got an average score of 81% with very decent criteria, based on the test response, junior high school students got an average score of 76% with interesting criteria.